Application of edible coatings on fresh and minimally processed vegetables: a review. Issue 3 (4th May 2019) - Sharma, Poorva; Shehin, V. P.; Kaur, Navpreet; Vyas, Pratibha
ABSTRACT: World population is increasing and expected to reach around 10.5 billion by 2050. To fulfil the requirement of future generations, food supplies need to increase. Increased production, improved distribution, and reduced losses can improve availability and accessibility of food. With the help of innovative postharvest technologies, agricultural industries are meeting production and intercontinental distribution demands of fresh produce. A critical component of ensuring global food security is reduction in postharvest food losses. Use of edible coating is a novel approach to improve the quality of food for consumer acceptance. Edible coatings are an eco-friendly technique, which slows deterioration of vegetables by controlling gas exchange, moisture transfer, and oxidation. Major advantage of these coatings is to improve nutritional and sensory quality of food by incorporating active ingredients into the polymer matrix that are consumed with food products. The aim of this review is to update information about edible coating on minimally processed and fresh vegetables, focusing on the composition, active ingredients, antimicrobial concentration and their effect on ripening rate, phytonutrients retention and shelf-life. This information will be helpful for processors to select the best coating material and its effective concentration for different fresh and minimal processed vegetables.